KEMASAN PRODUK SEBAGAI STRATEGI PEMASARAN KERUPUK RAMBAK “MIRASA” DI DESA DUKUHTURI, KEC. BUMIAYU, KAB. BREBES - Sulistyandari .; Ekaningtyas Widiastuti; Suci Indriati (ADIMAS Jurnal Pengabdian Kepada Masyarakat, 2017)
Community Service Activities this time was conducted in one type of SMEs namely Rambak Kerupuk "Mirasa" Dukuhturi Village, Bumiayu District, Brebes Regency. This dedication activity is in the form of counseling and business assistance, considering that this business is one of the business that has good potential good because it has high economic value, is a typical product of a region and its ability to help increase people's income. Production activities are still relatively simple and the marketing aspect is very simple. The product is  packed in an old fashioned way using only plastic containers that are stapled and have not used labels and ordinary cardboard with photocopy labels. Throughout the activity, the partners get counseling and business assistance from the Team. Partners have also successfully extended their PIRT business licenses for the next five years and have created new brand labels that can add value to their products. Packaging also no longer use ordinary staples but already using a sealer to package the product. This activity hopefully can provide benefits for partners in developing their business.